Sheikh Muhammad Walī Al-Khalidī’s Idea about the Education Concept of Tazkiyatun Nafsi - Rusdi Kurnia (Budapest International Research and Critics University, 2019)
This study aims to discuss about idea of Sheikh Muhammad Walī Al-Khalidī about the education concept of Tazkiyatun Nafsi. He was born in Blang Poroh Village, Labuhan Haji Subdistrict, South Aceh Regency, in 1338 H. Suluk is to train the teachings of ṭariqat to come true. This training is the beginning to be able to follow the Sunnah of the Messenger and hold the syariah'atnya and behave with his morals. When walking the path of suluk, a salik is given psycho-spiritual education from the mursyid. Every time, the mursyid always pays attention to the physical and non-physical situations and conditions found in the salik. This condition is a guide for the mursyid in guiding salik. This pattern of education will influence the mindset and remembrance pattern of a salik. Unnoticed by a salik that a murshid has formed a new psychology for salik to always get closer to Allah.